Health Care Problems and Ensuring Sustainable Development among Employees - Rostkowski, Tomasz (Edukacja Ekonomistów i Menedżerów, 2020)
The article offers a synthetic presentation of the results of analyses of diverse data resources and other scientific information concerning the healthcare in Poland. These studies were conducted in order to put forward positive changes that are not only to prevent the fall of the system, which is highly probable, but also to improve the availability of medical services and increase their quality. These studies are of major importance because the availability of medical (healthcare) services is largely determined by whether it is possible to implement the idea of sustainable development among employees, which indirectly determines the possibility of implementing sustainable development principles incorporated into legal circulation under one of the first articles of the Constitution of the Republic of Poland. The concept of sustainable development is not only one of the important reasons which call for modernisation of the functioning of the healthcare system, but also an idea which, once applied, may be helpful in solving healthcare problems. Considering the fact that the largest problem of this system in Poland lies in the shortage of employees, it becomes clear that by trying to ensure sustainable development of employees working in other industries, first, it is necessary to take care of their health, which must lead through sustainable development of healthcare workers. The aim of the article is to present the comprehensive nature of the idea of sustainable development of employees, the role of health protection in achieving a balance by employees, and to show the way to build integrated programmes to maintain the health of employees and their families against the background of the limitations of the Polish healthcare system.